AB0595 Evaluation of Cognitive Function by Electrophysiological Study in Systemic Lupus Erythematosus Patients with Previous Neuropsychiatric Involvement. (9th June 2015) - Gao, Y.; Cheung, T.F.; Gao, J.; Lau, E.; Wan, H.Y.; Mok, M.Y.
Abstract : Background: Previous studies on cognitive dysfunction evaluated by electrophysiological test in patients with systemic lupus erythematosus (SLE) who had previous neuropsychiatric involvement (NPSLE) were inconsistent. Objectives: This study aimed to evaluate P300 as an electrophysiological marker of cognitive function in NPSLE patients who were diagnosed to have cognitive impairment by standard neuropsychological tests. Methods: Event-related potentials (ERP) were assessed by the auditory and visual oddball paradigms. Amplitude and latency of P300 at the frontal (Fz), central (Cz) and parietal (Pz) regions were determined and compared to controls. Results: Sixteen patients with previous NPSLE were identified to have cognitive impairment, defined as one or more tests below 2 standard deviations of demographically normative data, among 20 patients recruited for comprehensive neuropsychological tests. P300 detection was performed in NPSLE patients with cognitive impairment (n=9), matched SLE patients without previous NPSLE (non-NPSLE) (n=9), and healthy controls (n=15). Auditory oddball task did not show any P300 abnormality between groups. Visual oddball task revealed reduced amplitude of P300 over Fz (p=0.002) and Cz (p=0.009) electrodes in NPSLE patients compared to healthy controls and among those who had predominant memory deficit (p=0.01 at Fz). Abnormal P300 was also observed in non-NPSLE patients at Fz and Cz. Conclusions: P300 elicited by auditory oddball paradigm was not a sensitive electrophysiological marker for cognitive impairment in NPSLE patients. Using visual oddball paradigm, abnormal P300 was found in NPSLE patients over frontal and parietal regions compared to normal controls but was not discriminative from possible subclinical disease in non-NPSLE patients. Disclosure of Interest: None declared